Association between shift work and insulin resistance in women: Implications for metabolic health - You-Jung Choi; Soo Hyeon Cho; Ja-Ho Leigh; Sung Hoon Jeong (PLoS ONE, 2025)
Shift work has been associated with circadian rhythm disruption and related metabolic disturbances, with women potentially being more vulnerable due to physiological and hormonal characteristics. Research on the correlation between shift work and insulin resistance in women outside hospital nursing settings remains scarce. Therefore, this study investigated the relationship between shift work and insulin resistance in working-age women, using the triglyceride-glucose (TyG) index as a surrogate marker. Data from 3,780 female participants aged 19–64 years were collected from the 2019–2021 Korea National Health and Nutrition Examination Survey. Participants were classified as day or shift workers, and insulin resistance was categorized as high or low based on the TyG index. The association between work schedule and insulin resistance was evaluated after adjusting for potential confounders. Shift workers had 1.30 times higher odds of elevated insulin resistance than day workers. Stronger associations were observed among women aged 40–50 years, those in pink-collar occupations, and individuals with adverse lifestyle factors, including overweight status, physical inactivity, alcohol consumption, and smoking. These findings underscore the importance of tailored workplace health interventions and the adoption of personalized, circadian rhythm–aligned strategies to reduce metabolic risk among female shift workers, thereby supporting occupational health policy and preventive care.